In silico identification of vaccine candidates against Klebsiella oxytoca. (August 2017) - Talukdar, Sandipan; Bayan, Udeshna; Saikia, Kandarpa Kr.
Graphical abstract: Highlights: Potential vaccine candidates against Klebsiella Oxytoca have been identified. A Reverse Vaccinology approach has been adopted. By using extensive computational tools the problems of conventional Vaccine production has been reduced. Abstract: Klebsiella oxytoca causes several diseases in immunocompromised as well as healthy individuals. Increasing resistance to a number of antibiotics makes treatment options limited. Prevention using vaccine could be an important solution to get rid of infections caused by Klebsiella oxytoca . In recent time, genome based approaches have contributed significantly in vaccine development. Our aim was to identify the most conserved and immunogenic antigens that can be considered as potential vaccine candidates. KEGG database was used to find out pathways unique to the bacteria. Subcellular localization of the protein sequences taken from the selected 36 pathways were predicted using PSORTb v3.0.2 and CELLO v2.5. Prediction of B cell epitope and the probability of the antigenicity were evaluated by using IEDB and Vaxijen respectively. BLASTp was done to find out the similarity of the selected proteins with the human proteome. Proteins failing to comply with the set parameters were filtered at each step. Finally, we identified 6 surface exposed proteins as potential vaccine candidates against Klebsiella oxytoca .